2018
DOI: 10.1039/c8ra08807a
|View full text |Cite
|
Sign up to set email alerts
|

A selective detection approach for copper(ii) ions using a hydrazone-based colorimetric sensor: spectroscopic and DFT study

Abstract: The development of an efficient and miniaturized analytical approach to determine trace levels of toxic ions in aqueous fluids presents a current research challenge. Hydrazone-based chemosensors are considered potential candidates due to their high sensitivity and selectivity towards heavy metal ions. Computational techniques can be properly implemented to elucidate possible modes of ligand-metal interaction and provide an in-depth understanding of the chemistry involved. The present study reports the use of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The charge transfer characteristics of any two interacting molecules are determined by the spatial orientation of their frontier orbitals, and the energy gap maintained therein. [ 47 ] Molecules having lower energy gaps exhibits higher charge transfer characteristics and are therefore predicted to be more reactive. Frontier orbital distribution of the adsorbents (Figure 12b ) showed that the HOMO‐LUMO orbitals were adequately distributed across the molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The charge transfer characteristics of any two interacting molecules are determined by the spatial orientation of their frontier orbitals, and the energy gap maintained therein. [ 47 ] Molecules having lower energy gaps exhibits higher charge transfer characteristics and are therefore predicted to be more reactive. Frontier orbital distribution of the adsorbents (Figure 12b ) showed that the HOMO‐LUMO orbitals were adequately distributed across the molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of Compound 1 was first energy minimized using B3LYP/6‐31 G* level of theory (Figure a‐c). And the 1 + Zn 2+ adduct as well as desillylated product were independently optimized under similar condition to explain metal ions as well as fluoride‐induced optical changes respectively . In free probe, the dihedral angle between two pyridine rings of bipyridine unit was found to be ∼30°, whereas, in presence of Zn 2+ it became 0.5°.…”
Section: Resultsmentioning
confidence: 99%
“…DFT and TD-DFT calculations 32 were performed on a PC with Processor Intel®Xeon (R) CPU E5-2650 v2@2.60 GHz × 32, RAM 16 GB, Hard disk SSD PCIe, and VGA Zotac GeForce GTX 1080TI AMP EXT CORE. The calculation was performed using the Gaussian 09 program 34 with B3LYP hybrid method 35 and a basis set of 6-311+G(d,p). To achieve the actual condition of experiments, the solvent effect of DMSO was included in the calculations employing Integral Equation Formalism Variant Polarizable Continuum Mode (IEFPCM).…”
Section: Methodsmentioning
confidence: 99%
“… 36 Calculation covered such parameters as, structural geometry and spectrum of infra-red, for the mechanism of interaction study, 36 and gap energy of HOMO–LUMO to study the stability of the chelate compound. 35 …”
Section: Methodsmentioning
confidence: 99%